Mysticism : its true nature and value: with a translation of the "Mystical theology" of Dionysius, and of the letters to Caius and Dorotheus (1, 2 and 5) - Sharpe, Alfred Bowyer (Sands, 1910)
I. Two ideas of mysticism.--II. Supernatural mysticism.--III. The nature of mystical experience.--IV. The object of mystical knowledge.--V. The psychology of mysticism.--VI. Evil.--VII. Immanence and transcendence.--VIII. Plotinus.--IX. Heretical mystics.--X. Mysticism, philosophy and religion.--XI. Dionysius.--XII. The "Mystical theology" of Dionysius the Areopagite.--Letter: I. To Caius the monk--The ignorance by means of which God is known is above sense-knowledge, not below it. II. To the same--In what sense God is above the principle of divinity. V. To Dorotheus the deacon--The divine darkness further explained.